'An indefatigable intermediary': Harold Woodbury Parsons (1882–1967) and the formation of the European collections at the Cleveland Museum of Art: part 2. (14th March 2020) - Rowlands, Eliot W
Abstract: O n 4 June 1925, Harold Woodbury Parsons was appointed European Representative to the Cleveland Museum of Art; for the remainder of the decade he distinguished himself in scouting for and acquiring masterworks of European art for the essentially brand new institution. His long-time contacts in Rome, to begin with, led him to a famous Byzantine ivory (formerly in the collection of Count Grigorij Stroganoff). This he bought for the museum in November 1925, winning enthusiastic praise from Paul J. Sachs, a key figure in American museological circles. Similarly, he acquired soon afterwards El Greco's Holy Family with St Mary Magdalen, despite intense competition. Parsons was ideally placed in the sale of Filippino Lippi's Holy Family tondo as a sometime agent for the antiquities collector Edward Perry Warren (recently deceased). Parsons's correspondence and unpublished notices in the Duveen Brothers records document the off-again, on-again dealing for what is now one of the pre-eminent Italian Renaissance paintings in America, acquired in August 1929.